Pneumopericarditis: A Case of Acute Chest Pain with ST Segment Elevation - Erwin E. Argueta; Menfil A. Orellana-Barrios; Teerapat Nantsupawat; Alvaro Rosales; Scott Shurmur (Case Reports in Cardiology)
Pneumopericarditis describes a clinical scenario where fluid and air are found within the pericardial space. Although infrequent, pneumopericarditis should be considered in patients presenting with acute chest pain as a differential diagnosis. This is relevant in patients with history of upper gastrointestinal (GI) surgery, as this may lead to a fistula communicating the GI tract and the pericardium. We report a 42-year-old man with history of numerous surgical interventions related to a Nissen fundoplication that presented with acute chest pain and inferior lead ST segment elevations. Emergent coronary angiography was negative for coronary vascular disease but fluoroscopy revealed air in the pericardial space. Subsequent radiographic studies helped confirm air in the pericardial space with a fistulous communication to the stomach. Ultimate treatment for this defect was surgical closure.